2015
DOI: 10.1016/j.alcohol.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent ethanol inhalation increases ethanol self-administration in both C57BL/6J and DBA/2J mice

Abstract: Inbred mouse strains provide significant opportunities to understand the genetic mechanisms controlling ethanol-directed behaviors and neurobiology. They have been specifically employed to understand cellular mechanisms contributing to ethanol consumption, acute intoxication, and sensitivities to chronic effects. However, limited ethanol consumption by some strains has restricted our understanding of clinically relevant endpoints such as dependence-related ethanol intake. Previous work with a novel tastant-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 65 publications
4
27
1
Order By: Relevance
“…Nonetheless, these LORR data also bear upon our finding that females failed to show an increase in ethanol drinking after CIE, even under exposure conditions that produced clear increases in males (as had been reported in earlier studies [Becker & Lopez, 2004; Carrara-Nascimento et al, 2013; Dhaher et al, 2007; Finn et al, 2007; Griffin, Lopez, & Becker, 2009; Griffin, Lopez, Yanke, et al, 2009; Holmes et al, 2012; Lopez & Becker, 2005; McCool & Chappell, 2015]). This finding resembles an earlier report that females from high- and low-ethanol-preferring selected lines did not increase drinking after CIE, though males from these lines (unlike C57BL/6J males) also failed to do so (Lopez et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nonetheless, these LORR data also bear upon our finding that females failed to show an increase in ethanol drinking after CIE, even under exposure conditions that produced clear increases in males (as had been reported in earlier studies [Becker & Lopez, 2004; Carrara-Nascimento et al, 2013; Dhaher et al, 2007; Finn et al, 2007; Griffin, Lopez, & Becker, 2009; Griffin, Lopez, Yanke, et al, 2009; Holmes et al, 2012; Lopez & Becker, 2005; McCool & Chappell, 2015]). This finding resembles an earlier report that females from high- and low-ethanol-preferring selected lines did not increase drinking after CIE, though males from these lines (unlike C57BL/6J males) also failed to do so (Lopez et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Previous work has described an array of neural and behavioral effects of CIE in male mice of several strains (though predominantly C57BL/6J) and various lines of male or sex-balanced groups of gene mutant mice (Becker, 2013). The reported behavioral effects of CIE in mice include elevated ethanol drinking (Becker & Lopez, 2004; Carrara-Nascimento, Lopez, Becker, Olive, & Camarini, 2013; Dhaher, Finn, Snelling, & Hitzemann, 2007; Finn et al, 2007; Griffin, Lopez, & Becker, 2009; Griffin, Lopez, Yanke, Middaugh, & Becker, 2009; Holmes et al, 2012; Lopez & Becker, 2005; McCool & Chappell, 2015), increased seizure susceptibility and anxiety-like behavior (Becker, 1994; Becker, Diaz-Granados, & Hale, 1997; Becker, Diaz-Granados, & Weathersby, 1997; Becker & Hale, 1993; Morales et al, 2015), tolerance to acute ethanol intoxication (Daut et al, 2015), and alterations in appetitive and aversive learning (DePoy et al, 2013, 2015; Holmes et al, 2012; Radke et al, 2015). In terms of sex differences, one study reported that male but not female HAP-2 mice showed increased ethanol drinking and withdrawal signs following CIE (Lopez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, others have shown that DBA/2J self-administer significantly higher levels of ethanol if ethanol is delivered intragastrically (Fidler et al, 2011) or when ethanol is gradually introduced along with masking its taste with monosodium glutamate (MSG) (McCool & Chappell, 2014, 2015). In this study, the use of a sucrose fading or a MSG fading procedure was omitted to avoid masking the initial intake level of C57BL/6J, DBA/2J and the different BXD strains.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile experiments to reveal its possible effects on animals are still being conducted. Artificial flavor enhancers such as MSG may cause animals to display behaviors similar to anxiety, epilepsy, and depression (17)(18)(19)(20)(21). Behaviors similar to anxiety can be identified by the means of experimental open field test, light/dark transition test, elevated plus maze test, tail suspension test, forced swim test, and social interaction task (22).…”
Section: Discussionmentioning
confidence: 99%